2005
DOI: 10.1074/jbc.m411523200
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Protein-tyrosine Phosphatases by Mild Oxidative Stresses Is Dependent on S-Nitrosylation

Abstract: Previous studies have shown that a Ca2؉ -dependent nitric-oxide synthase (NOS) is activated as part of a cellular response to low doses of ionizing radiation. Genetic and pharmacological inhibitor studies linked this NO signaling to the radiation-induced activation of ERK1/2. Herein, a mechanism for the radiation-induced activation of Tyr phosphorylation-dependent pathways (e.g. ERK1/2) involving the inhibition of protein-Tyr phosphatases (PTPs) by S-nitrosylation is tested. The basis for this mechanism reside… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
85
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 125 publications
(92 citation statements)
references
References 64 publications
6
85
0
Order By: Relevance
“…It is proposed that ROS induces PTP inactivation by reversible oxidation of thiol groups to form disulfide bonds (Denu and Tanner, 1998), which are picked up by the redox-sensing proteins such as thioredoxin or glutathione, which restore the PTP activities by reducing oxidized PTPs (Reth, 2002). In addition to oxidation, S-nitrosylation of PTP has been suggested as a mechanism of PTP inhibition induced by mild oxidative stress (Barrett et al, 2005). We cannot rule out the possibility that SHP1 or CD45 undergoes Snitrosylation on TNF-a or H 2 O 2 treatment in T cells under the assay conditions employed, which may later proceed to oxidation to sulfenic acid formation.…”
Section: Discussionmentioning
confidence: 99%
“…It is proposed that ROS induces PTP inactivation by reversible oxidation of thiol groups to form disulfide bonds (Denu and Tanner, 1998), which are picked up by the redox-sensing proteins such as thioredoxin or glutathione, which restore the PTP activities by reducing oxidized PTPs (Reth, 2002). In addition to oxidation, S-nitrosylation of PTP has been suggested as a mechanism of PTP inhibition induced by mild oxidative stress (Barrett et al, 2005). We cannot rule out the possibility that SHP1 or CD45 undergoes Snitrosylation on TNF-a or H 2 O 2 treatment in T cells under the assay conditions employed, which may later proceed to oxidation to sulfenic acid formation.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, in stimulated macrophages that produce H 2 O 2 on the outside of the cell, H 2 O 2 -dependent PTP1B glutathionylation occurs, although the rate constant for formation of the sulfenic acid intermediate suggests that it would not be the intermediate [120,121]. PTP1B, PTP, PTEN and SHP2 are also substrates for inhibitory S-nitrosylation [1,[122][123][124][125][126][127], and singlet oxygen also inactivates protein tyrosine phosphatase-1B by oxidation of the active site cysteine [128], demonstrating that this class of proteases is a target for inhibition via multiple cysteine oxidations.…”
Section: Regulation Of Tyrosine Phosphatasesmentioning
confidence: 99%
“…Nedospasov et al 103 compounds such as nitroso glutathione 98 . The S-nitrosylation of some protein tyrosine phosphatases (PTPs) has been demonstrated 102,[104][105][106] . It should be noted that even though NO mediates inactivation of PTP1B 104,106,107 , it can be reactivated by chemical treatment with dithiothreitol, but there is nothing known about possible natural occurring systems that may reactivate the SNO modified proteins.…”
Section: Protein Cysteine S-nitrosylationmentioning
confidence: 99%
“…In fact, a general examination of the 100 or so proteins that have been shown to be S-nitrosylated in biological systems, see for example [99][100][101] , have demonstrated that they have a degenerate consensus motif as such X(K/R/H)C(D/E). Thus the target cysteine is juxtaposed between a basic amino acid on one side, and an acidic amino acid on the other side 102 . It should be noted that the consensus motif can be accomplished by juxtaposing the basic and acidic amino acids near the target cysteine, either spatially as dictated by the protein conformation, or in a defined linear sequence.…”
Section: Protein Cysteine S-nitrosylationmentioning
confidence: 99%